Letter to editor NEONATAL NERVE PALSIES: A CONTEMPORARY OBSTETRIC PERSPECTIVE - Roberts, Darren J.; Svigos, and John M. (BALI MEDICAL JOURNAL, 2014)
Background: Birth trauma and its often incorrect inference of iatrogenic causation has led to unfortunate implications for the affected child, the parents, the obstetrician and the midwife due to unwarranted medico-legal attention in our current litigious society. A more discerning evaluation of neonatal nerve palsies following labour and delivery has led to a better understanding of their aetiology with potentially more appropriate outcomes for all parties involved.
Keywords: birth trauma, iatrogenic, medico-legal, aetiology